Transport of moderately relativistic electron beam in dense plasma. (17th June 2019) - Li, R; Zhou, C T; Yu, M Y; Ruan, S C; He, X T
Abstract: Transport of moderate relativistic micro electron beam in overdense plasma is investigated using numerical simulation and analytical modeling. It is found that if the product of the initial beam current density j b and radius R 0 is above a lower limit, which scales like ( j b R 0 ) lim ∝ n e, where n e is the plasma density, the beam will periodically self pinch and relax as it propagates. Otherwise the beam diverges. But if j b R 0 is too large, the pinching behavior becomes quite different. Such micro-beam transport behavior can be attributed to the nonlinear dynamics of the beam electrons in overdense plasma.